Food production, environment, and mobility among Late Iron Age Nguni-speakers of South Africa. (20th February 2022) - Jimenez, Raevin
Abstract: During the Late Iron Age, early Nguni-speaking farmers entered and moved across the region of the lower Thukela uplands through frequent, short-range episodes of population movement. As they did so, they innovated new food production technology, altered the landscape, and adapted to ecological conditions. The article presents comparative historical linguistic evidence for the history of farming and interaction with the environment among Nguni-speakers between c. 900–1052 CE. Analysis shows the ways Nguni-speaking farmers responded to environmental conditions through landscape engineering and social engineering, including population dispersal.